Evaluasi dan Arahan Peningkatan Kualitas Infrastruktur Permukiman: Studi Kasus Permukiman Pesisir Perkotaan Kelurahan Buol, Kabupaten Buol - Basri, I. Setiawan; Arifin, R.; Akhmad, A. Gani; Romanda, R.; Salenda, H. (Jurusan Teknik Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 94118 e-mail :Jurusan Arsitektur, Fakultas Teknik Universitas Tadulako Kampus Bumi Tadulako Tondo Jl. Sukarno-Hatta Km.9, Palu 941, 2025)
The development of urban coastal areas presents many challenges, including limited access to basic infrastructure services and vulnerability to natural disasters. This study aims to evaluate the quality of coastal settlement infrastructure in Buol, with a focus on Buol Village in the Biau subdistrict. Buol Village is also the capital of Buol Regency. The results provide recommendations for policy directions on settlement development that are adaptive to the coastal environment. The research method uses a descriptive, quantitative, evaluative case study approach. The study results indicate that the majority of infrastructure facilities are rated